Orthopedic Trauma During Pregnancy; a Narrative Review - Jafari Kafiabadi, Meisam; Sabaghzadeh, Amir; Khabiri, Seyyed Saeed; Sadighi, Mehrdad; Mehrvar, Amir; Biglari, Farsad; Ebrahimpour, Adel (Archives of Academic Emergency Medicine, 2022)
Introduction: Blunt traumas, like road accidents and falls, are common causes of injuries to pregnant women, and the major risk factors are young age and low socioeconomic level. Due to physiological and anatomical changes specific to pregnancy, such as changes in blood pressure and hemoglobin drop, trauma management involves certain complexities. Physical trauma is estimated to cause at least 1 complication in every 12 pregnancies. This study aims to evaluate orthopedic trauma during pregnancy and appreciate the different approaches to circumvent the resultant challenges. Methods: We reviewed 55 articles, published on orthopedic trauma during pregnancy between 2011 and 2021. The articles were identified by searching PubMed, google-scholar, Scopus, and Science-Direct. We utilized the search terms: fall in pregnancy, traumas in pregnancy, motor vehicle accident/crash in pregnancy, blunt trauma in pregnancy, pregnant trauma patient, penetrating injury during pregnancy, assault, interpersonal violence in pregnancy, and mortality and pregnancy. Results: According to available reports, after stabilizing the pregnant patient, diagnostic procedures, including radiography, and even gadolinium-based techniques when needed, can be performed to examine extensive trauma. In contrast to elective orthopedic surgery, emergency orthopedic surgeries, including reduction of open fractures, should be performed promptly. Conclusion: Based on our investigation, pregnant women with orthopedic injuries that are severe, or even seemingly less severe, experience significantly increased adverse pregnancy outcomes, which include preterm birth, placental abruption, poor infant condition at birth, infant death, and even maternal death.